(untitled) (Journal of Parents and Teachers, 2016)
The following article deals with the conceptions of the current education, the comparisons between the old and the new education. There is a reference to the lack and the characteristics of the educational system and teaching’s models that teachers are doing in the school and the relationships with the students. The author goes deep with examples and concepts related to education to everything that is related to the behaviors and the teaching received by the students in the schools.